First Order FBGs in InF3Fibre Inscribed by Interferometry Technique and UV-fs-Laser - Chiamenti, Ismael; Elsmann, Tino; Reupert, Aaron; Kara, Oguzhan; Becker, Martin; Wondraczek, Lothar; Chernysheva, Maria (2021 Conference on Lasers and Electro-Optics, CLEO 2021 - Proceedings, 2021)
First order FBGs were inscribed in InF3 fibre by UV-fs-laser and interferometry technique. The spectral quality and good thermal stability of the gratings will contribute to the development of Mid-IR all-fibre laser technology.
CRIS-Team Scopus Importer:2023-04-20